Understanding Pre-Exposure Prophylaxis Use in the United States and the Potential Impact of Community Pharmacies - Fulcher, Jacinda Tran (My University, 2024)
The US HIV epidemic is characterized by notable geographic, racial, and socioeconomic disparities and substantial health and economic burden. Pre-exposure prophylaxis (PrEP) is a safe, effective therapy to prevent the acquisition of HIV, but uptake remains low, partly due to inadequate access to PrEP providers. Community pharmacies are well-positioned to expand access for populations disproportionately impacted by the HIV epidemic. This dissertation leverages several modeling methods to examine population-level factors driving PrEP utilization and the potential impact of community pharmacies for expanding PrEP access nationwide. First, I trained a robust set of machine learning models to explore population-level characteristics and social determinants of health that were most predictive of county-level PrEP use across the US. The best performing model highlighted the importance of county HIV prevalence and testing rates, access to healthcare facilities and providers, healthy lifestyle indicators (e.g., access to exercise facilities, obesity rates), and sociodemographic factors (e.g., racial composition, income, education). This exploratory, ecological analysis sets the stage for further investigations into the relationships between identified predictors and PrEP utilization, ultimately informing potential population-level strategies or policies to promote PrEP uptake. Furthermore, prompted by recent state legislation permitting community pharmacy-based PrEP, my second and third aims assessed the potential impact of a hypothetical federal policy empowering pharmacists to initiate PrEP for eligible individuals. My nationwide examination of geospatial access to PrEP providers and community pharmacies in 2022 demonstrated that community pharmacies could expand access in 78.2% to 94.3% of census tracts that currently lack PrEP access, potentially benefitting 34.7 to 41.0 million US residents and alleviating geographic and racial disparities in PrEP access. Lastly, I adapted an infectious disease model to simulate plausible pharmacy-based PrEP scenarios in the Atlanta metropolitan area, a region with high HIV burden. I concluded that community pharmacy-based PrEP could substantially improve health outcomes in terms of quality-adjusted life-years gained and HIV cases averted and would be cost-saving or cost-effective over a 50-year time horizon. Overall, the work presented in this dissertation provides insight into predictors of PrEP utilization in the US and the potential impact and value of community pharmacies for bridging gaps in PrEP access.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Pharmaceutical sciences; Public health; Health sciences; To Be Assigned